Food Security and Climate Change to 2050: Cambodia, A Policy Discussion Paper - Magnan N; Thomas, Timothy S. (Cambodia Development Resource Institute (CDRI), 2011)
Cambodia s population and economy are highly vulnerable to climate change. Food security is already a major concern in Cambodia, where 25 percent of the population suffered from undernourishment in 2004-2005, a higher proportion than in neighboring Southeast Asian countries (Shicavone2010).1 Some 80 percent of Cambodia s population is rural and agriculture accounts for 35 percentof GDP (World Bank 2009). Two-thirds of Cambodia s population is economically dependent onagriculture (FAO 2010; Shicavone 2010), and most farmers are poorly equipped to adapt to climatechange (Royal Government of Cambodia 2006).